RESENTMENT – EXCAVATING A RESURGENT PHENOMENON IN CONTEMPORARY SOCIETY - Balcomb, Anthony (Scriptura, 2021)
Resentment is a powerful human emotion that has both private and social dimensions where it manifests in a variety of ways. It has been identified as the force behind uprisings against racial, economic, and political inequality and injustice throughout time, as well as in the contemporary scene. Its moral and socio-political implications have been reflected on ever since Nietzsche identified it as a major contributing factor in the genealogy of morality. Max Scheler made a brilliant phenomenological analysis of it, and Francis Fukuyama recently identified it as a significant force in shaping contemporary identity politics. It has become a significant political force in contemporary South Africa, where the politics of reconciliation have largely been displaced by the politics of resentment. Although it has generally been viewed as having negative consequences for the social compact, its moral justification in specific circumstances has been powerfully made by the holocaust survivor Jean Amery and more recently by Didier Fassin with regard to post-apartheid South Africa. However, it is often accompanied by what Nietzsche called the "falsification of the tablets of value", which also means that it may lead to alternative mental constructions of reality that might result in delusional perspectives that can have dire social and moral consequences.